Tenascin-C is an endogenous activator of Toll-like receptor 4 that is essential for maintaining inflammation in arthritic joint disease. - Midwood, K; Sacre, S; Piccinini, A; Inglis, J; Trebaul, A; Chan, E; Drexler, S; Sofat, N; Kashiwagi, M; Orend, G; Brennan, F; Foxwell, B (2009)
Although there have been major advances in the treatment of rheumatoid arthritis with the advent of biological agents, the mechanisms that drive cytokine production and sustain disease chronicity remain unknown. Tenascin-C (encoded by Tnc) is an extracellular matrix glycoprotein specifically expressed at areas of inflammation and tissue damage in inflamed rheumatoid joints. Here we show that mice that do not express tenascin-C show rapid resolution of acute joint inflammation and are protected from erosive arthritis. Intra-articular injection of tenascin-C promotes joint inflammation in vivo in mice, and addition of exogenous tenascin-C induces cytokine synthesis in explant cultures from inflamed synovia of individuals with rheumatoid arthritis. Moreover, in human macrophages and fibroblasts from synovia of individuals with rheumatoid arthritis, tenascin-C induces synthesis of proinflammatory cytokines via activation of Toll-like receptor 4 (TLR4). Thus, we have identified tenascin-C as a novel endogenous activator of TLR4-mediated immunity that mediates persistent synovial inflammation and tissue destruction in arthritic joint disease.